An Analysis of Criminology as a Profession in the Republic of South Africa - Mphatheni, Mandlenkosi Richard; Nkosi, Sphamandla Lindani; Tutu, Owethu Johnson; Gopal, Nirmala (International Journal of Criminology and Sociology, 2022)
The professionalisation of criminology has not been a smooth process in South Africa. The literature reveals that it has been a slow process burdened with numerous challenges. The slow process of professionalising criminology has caused uncertainty about criminology as a profession. Although, South African universities have taken the significant steps towards recognising criminology as an academic discipline. This systematic review studied various sources to justify the inability of relevant structures to professionalise criminology. Moreover, it endeavoured to understand the extent to which criminology has been professionalised in South Africa. This critical analysis confirms that the process of professionalising criminology has been prolonged and that it has been fraught with challenges. Results of this study are relevant for any idea to restructure the criminology, and it is envisaged that appropriate structures may find results useful in altering the vision of the profession. This paper recommends that an independent professional board be established to assist and guide criminologists. Such a board could, for instance, suggest a constructive structure and broadly define the role and functions of criminologists within the South African context.